Chile - Hintz, Martin (Chicago : Childrens Press, 1985)
Describes the landscape, history, economy, culture, and people of this extraordinarily long, narrow country.
Includes index.
6.
7.4
5-8
5-9.
Keywords: Chile -- Juvenile literature; Chile; Chile